September sneakers - Roy, Ron, 1940- (Roy, Ron, 1940- Calendar mysteries., 2013)
Someone has been stealing and leaving behind little green sneakers, so Bradley, Brian, Nate, and Lucy trail their new teacher, who wears the same shoes in normal size.